2023
DOI: 10.1186/s13613-023-01143-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with circulatory death after out-of-hospital cardiac arrest: a population-based cluster analysis

Abstract: Background Out-of-hospital cardiac arrest (OHCA) is a common cause of death. Early circulatory failure is the most common reason for death within the first 48 h. This study in intensive care unit (ICU) patients with OHCA was designed to identify and characterize clusters based on clinical features and to determine the frequency of death from refractory postresuscitation shock (RPRS) in each cluster. Methods We retrospectively identified adults admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Paul et al [ 30 ] reported that the majority of subjects with very high Cardiac Arrest Hospital Prognosis (CAHP) scores, which included epinephrine dose and six other variables, were more likely to die of PRS. Binois et al [ 17 ] identified a cluster of patients strongly associated with PRS whose epinephrine dose was notably much higher than others. In this study, we were able to show that this association was not only associated with PRS but also responsible for early mortality from cardiocirculatory causes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Paul et al [ 30 ] reported that the majority of subjects with very high Cardiac Arrest Hospital Prognosis (CAHP) scores, which included epinephrine dose and six other variables, were more likely to die of PRS. Binois et al [ 17 ] identified a cluster of patients strongly associated with PRS whose epinephrine dose was notably much higher than others. In this study, we were able to show that this association was not only associated with PRS but also responsible for early mortality from cardiocirculatory causes.…”
Section: Discussionmentioning
confidence: 99%
“…Patients meeting the criteria for more than one mode of death category were classified according to the primary reason for death. In a previous SDEC work (from 2011 to 2018), we highlighted that the agreement between the two investigators regarding the classification of the mode of death was considered good (kappa coefficient 0.87) [ 17 ]. Secondary endpoints were the survival rate and the time to death according to the mode of death.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation